Analisis Kelayakan Usaha Ternak Ayam Ras Petelur Di Desa Cemerlang Kecamatan Masama Kabupaten Banggai : Feasibility Analysis Of Layer Chicken Business In Cemerlang Village Masama District, Banggai District - Husen, Sri Rahayu (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2021)
The formulation of the problem in this study was that laying hens in Cemerlang Village, Masama District, Banggai Regency were feasible to develop, the type of data used in this study was quantitative data. The source of data used in this study is primary data obtained by collecting data by the author in Cemerlang village and the business office of laying hens, to answer the problems in this study, the authors use several analytical methods including using cost analysis with the TC formula = VC+FC, second is revenue analysis with the formula TR = P x Q third is income analysis with the formula Revenue/Profit = TR (Total Revenue) – TC (Total Cost) and the fourth analysis that the author uses is R/C Ratio Analysis which is based on research results that total revenue Laying hens Rp. 1,80,000,000 and a total cost of Rp. 80,280,000. From the feasibility results it is known that the laying hen business is feasible to be developed with an R/C Ratio value of 2.2, meaning that the laying hen business is very profitable, so it is feasible to be developed by the community in Sepuratan, Cemerlang village, Masama sub-district, Banggai regency.